Ex-situ bioremediation of hydrocarbon contaminated soil using the biopile technique - Van Zyl, Helena Dorathea (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1998.